Among healthy term infants, is delayed cord clamping superior to usual practice for preventing clinically significant anemia at 6 months of age?. Issue 1 (January 2016) - Boehmer, Steven; Quiroz, Armando
Abstract : Evidence‐Based Answer : Delaying cord clamping (DCC) longer than 1 minute after delivery of the infant's shoulders appears to increase hemoglobin levels at 24 to 48 hours, but increases the risk of phototherapy for jaundice (SOR: A, meta‐analysis of RCTs). Hemoglobin levels at 3 to 6 months do not significantly differ between infants in the early cord clamping (ECC) and DCC groups, but iron deficiency is twice as likely at 6 months of age in the ECC group (SOR: C, meta‐analysis of RCTs of diseaseoriented outcomes).